2023
DOI: 10.1021/acs.jafc.3c02397
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variation of Residual Cortisol Obstructs Nutrient Acquisition in Animal-Derived Foods by Perturbing Glycerophospholipid Metabolism

Abstract: Cortisol is inevitably secreted by pigs due to the physical and psychological stressors produced by mixed group transportation and preslaughter handling. Accumulated cortisol in animal tissues enters the human body through the food chain and entails potential risks to human health. An integrated lipidome and proteome analysis was conducted to investigate the effect of the spatiotemporal variation of residual cortisol on nutrient acquisition in pork. A total of 55 crucial lipid molecules associated with cortiso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…14,15 Alterations in the composition, distribution, and metabolism of PLs in cells, tissues, and body fluids are associated with diseases. 16 Several studies have demonstrated that lipid metabolism is disturbed in obese mice. However, the changes in the levels and spatial distribution of lipids, especially phospholipids, in kidneys are unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Alterations in the composition, distribution, and metabolism of PLs in cells, tissues, and body fluids are associated with diseases. 16 Several studies have demonstrated that lipid metabolism is disturbed in obese mice. However, the changes in the levels and spatial distribution of lipids, especially phospholipids, in kidneys are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, differential expression of 44 lipid molecular species was observed in the adipose tissue of obese mice using matrix-assisted laser desorption ionization mass spectrometry imaging (MALDI–MSI) . Lipids play an essential role in the kidney by occupying about 3% of the wet weight, of which phospholipids account for more than 50%. , Alterations in the composition, distribution, and metabolism of PLs in cells, tissues, and body fluids are associated with diseases . Several studies have demonstrated that lipid metabolism is disturbed in obese mice.…”
Section: Introductionmentioning
confidence: 99%